Below-Ms austempering to obtain refined bainitic structure and enhanced mechanical properties in low-C high-Si/Al steels. (February 2016) - Zhao, Leijie; Qian, Lihe; Meng, Jiangying; Zhou, Qian; Zhang, Fucheng
Abstract: A novel heat-treatment process, below- Ms austempering, was performed on two low-C high-Si/Al steels, and accordingly the resultant microstructures and mechanical properties were investigated. The results showed that bainitic transformation occurs at isothermal temperatures below Ms and unexpectedly, the transformation process is accelerated significantly by the prior formation of martensite. Furthermore, as compared with the conventional above- Ms austempering process, the below- Ms austempering refines effectively the bainitic plates and reduces the size and volume fraction of blocky martensite/austenite phases, giving rise to much enhanced impact toughness and improved tensile properties. Graphical abstract: